A Bibliometric Analysis and Visualisation of Research Trends in Titanium-Based Orthopaedic Implants - Singh , Gurmeet (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Titanium is one of the widely used metal for orthopaedic implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Titanium-based orthopaedic implants”. All published articles related to “Titanium-based orthopaedic implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “Titanium-based orthopaedic implants” and also to find out the trends related to the same. The most active journal related to this research domain was Biomaterials. The most active country was the United States of America. The leading organization engaged in research regarding Titanium Based orthopaedic implants was the Brown University of the United States of America and the Chinese Academy of Sciences of China. The most active authors who had made valuable contributions related to orthopaedic implants were Webster T.J.